2016
DOI: 10.1002/jcb.25560
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Osteoclast; Far and Beyond Bone Resorption

Abstract: The accepted function of the bone resorbing cell, osteoclast, has been linked to bone remodeling and pathological osteolysis. Emerging evidence points to novel functions of osteoclasts in controlling bone formation and angiogenesis. Thus, while the concept of a "clastokine" with the potential to regulate osteogenesis during remodeling did not come as a surprise, new evidence provided unique insight into the mechanisms underlying osteoclastic control of bone formation. The question still remains as to whether o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Bone turnover (including bone formation and resorption phase) were regulated by the bone remodeling process, and any disturbance in this process will lead to osteopathic disease [ 24 , 41 ]. The postmenopausal osteoporosis was recognized as high bone turnover rate, which was characterized by the increased bone turnover markers [ 5 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone turnover (including bone formation and resorption phase) were regulated by the bone remodeling process, and any disturbance in this process will lead to osteopathic disease [ 24 , 41 ]. The postmenopausal osteoporosis was recognized as high bone turnover rate, which was characterized by the increased bone turnover markers [ 5 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous study reported that, in order to maintain the calcium homeostasis, the bone turnover process could be accelerated by a decrease of serum calcium content [ 35 , 41 ] and also sufficient calcium intestinal absorption is critical for reduction of bone turnover rate and alleviation of osteoporosis [ 2 ]. Our results indicated that CBP-Ca could significantly increase the intestinal absorption, bioavailability of calcium, and serum calcium, then decrease bone turnover rate, and thus ameliorate osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoclasts are derived from bone marrow monocytes/macrophages. Under physiological conditions, monocytes/macrophages first commit to macrophage colony-stimulating factor receptor-positive osteoclast precursor cells and then differentiate into receptor activator of nuclear factor κB-positive (RANK + ) tartrate-resistant acid phosphatase (TRAP + ) mononuclear preosteoclasts and eventually fuse to form mature multinuclear osteoclasts (39)(40)(41)(42)(43)(44)(45). Serving as precursors for osteoclasts, preosteoclasts have limited bone-resorbing activity.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclasts, which differentiate from osteoclast precursor cells and can fuse with peripheral mononuclear cells, are cells involved in bone resorption [ 15 ]. BMMs are considered to be osteoclast precursor cells and can differentiate into osteoclast-like multinucleated cells in vitro via the synergistic actions of RANKL and M-CSF [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%